Evoljucija organov gosudarstvennoj vlasti v sfere upravlenija fiziceskoj kul'turoj i sportom v nacale XX veka i v sovetskoj period - Zuev, V. N. (Teorija i Praktika fiziceskoj Kul'tury, 2004)
The government bodies, together with other power structures of administration are representing the state. They are the carriers of the government, through their activity the superpower state officials carry out the political authority.